2011
DOI: 10.1158/1078-0432.ccr-10-3262
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Administration of TLR4 Agonist Absorbed into a Cellular Vector Improves Antitumor Responses

Abstract: Purpose Since TLR agonists have been well characterized as DC activators, we hypothesized that the admixture of TLR4 agonist into a cellular vector could improve the anti-tumor response in vivo. Experimental Design GM-CSF secreting whole cell tumor cell vector (GVAX) was formulated with LPS, a TLR4 agonist, and its intratumoral therapeutic efficacy was tested in three different murine models. We utilized immunohistochemistry, FACS, ELISPOT, and in vivo CTL analysis to assess both local innate immune response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…Elispot assay was performed according to the instructions of the instrument manufacturer and as described before (21). Enzyme-linked immunosorbent spot (ELISPOT) plates (MABTECH AB-plus; Sweden, Product code: 3321-4APT-4) were washed 4 times with sterile PBS (200μl/well) and incubated with medium containing 10% serum for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Elispot assay was performed according to the instructions of the instrument manufacturer and as described before (21). Enzyme-linked immunosorbent spot (ELISPOT) plates (MABTECH AB-plus; Sweden, Product code: 3321-4APT-4) were washed 4 times with sterile PBS (200μl/well) and incubated with medium containing 10% serum for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that i.t. treatment with GVAX (GM-CSF secreting whole-cell tumor cell vaccine) plus LPS (TLR-4 agonist) was more efficient at generating anti-tumor responses than GVAX alone [58]. An i.t.…”
Section: It Immunotherapy With Synthetic Immunoagonistsmentioning
confidence: 99%
“…One mechanism that may account for the limited efficacy observed in many clinical trials is the lack of co-stimulation in the setting whereby DCs encounter the transferred tumor cells. In vaccination more generally, toll-like receptor (TLR) ligands have been used as adjuvants to activate the innate immune system and potentiate downstream immunity, and recently they have been added to enhance the effectiveness of whole cell tumor vaccine formulations 14 . The limited success of whole cell vaccines may also be secondary to diffuse cellular localization and short-term survival post adoptive transfer.…”
Section: Introductionmentioning
confidence: 99%